The new Bretton Woods from the perspective of Game Theory - Cadena, Juan Pablo (2007)
For the author, the principle character of the current world economic system is the enormous and growing current account deficit of the United States that serves as the motor for the dynamism of the world economy, and above all, for the sustained growth of the emerging economies, such as China. Using game theory, Cadena seeks to determine whether this economic system is sustainable over time.